2012
DOI: 10.1021/ol302298k
|View full text |Cite
|
Sign up to set email alerts
|

New WS9326A Congeners from Streptomyces sp. 9078 Inhibiting Brugia malayi Asparaginyl-tRNA Synthetase

Abstract: Lymphatic filariasis is caused by the Brugia malayi parasite. Three new congeners of the depsipeptide WS9326A (1), WS9326C (2), WS9326D (3) and WS9326E (4), were isolated from Streptomyces sp. 9078 by using a B. malayi asparaginyl-tRNA synthetase (BmAsnRS) inhibition assay. WS9326D specifically inhibits the BmAsnRS, kills the adult B. malayi parasite, and does not exhibit significant general cytotoxicity to human hepatic cells, representing a new lead scaffold for antifilarial drug discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 17 publications
2
62
0
Order By: Relevance
“…Taken together, the extensive NMR analysis finally allowed the unambiguous assignment of the 7 structure (Figure 1a). The 1 H NMR data were similar to those of 2, and comparison of partial 13 C NMR data with those of 2 confirmed their close similarity except for the signals of C-1 and C-3, which were up-field shifted from δ C 160.1 and 145.7 in 2 to δ C 137.6 and 122.5 in 8, respectively (Tables 1,2 and 3). Considering the 1 H NMR data and molecular formula of 8, we suggested these two carbons might be connected to a secondary amine, which was further confirmed by the correlations from H-3 (δ H 7.53) to C-1 (δ C 137.6), C-3a (δ C 122.0), C-4 (δ C 178.9) and C-9a (δ C 116.7), and from H 3 -10 (δ H 2.55) to C-1 (δ C 137.6), C-9 (δ C 186.3) and C-9a (δ C 116.7) in the HMBC spectrum.…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…Taken together, the extensive NMR analysis finally allowed the unambiguous assignment of the 7 structure (Figure 1a). The 1 H NMR data were similar to those of 2, and comparison of partial 13 C NMR data with those of 2 confirmed their close similarity except for the signals of C-1 and C-3, which were up-field shifted from δ C 160.1 and 145.7 in 2 to δ C 137.6 and 122.5 in 8, respectively (Tables 1,2 and 3). Considering the 1 H NMR data and molecular formula of 8, we suggested these two carbons might be connected to a secondary amine, which was further confirmed by the correlations from H-3 (δ H 7.53) to C-1 (δ C 137.6), C-3a (δ C 122.0), C-4 (δ C 178.9) and C-9a (δ C 116.7), and from H 3 -10 (δ H 2.55) to C-1 (δ C 137.6), C-9 (δ C 186.3) and C-9a (δ C 116.7) in the HMBC spectrum.…”
Section: Resultssupporting
confidence: 56%
“…Initial interpretation of the MS, 1 H NMR, 13 C NMR, HSQC and HMBC spectra (Figure 1b) suggested that the structure of 1 was similar to a The ultraviolet (UV) and infrared spectroscopy (IR) spectra of 2 resembled those of 1, and most of the 1 H and 13 C NMR data of 2 were highly similar to those of 1 (Tables 1 and 2). In the 1 H NMR, 13 C NMR and HSQC spectra of 2, additional signals attributed to a methoxyl group (δ H 3.87 and δ C 60.5) were observed, indicating one hydroxyl group in the A-ring was replaced by a methoxyl group. This was confirmed by the HMBC correlations from 7-OCH 3 to C-7 (δ C 139.9) and from 8-OH (δ H 13.18) to C-7 (δ C 139.9), C-8 (δ C 158.0) and C-8a (δ C 112.5; Figure 1b), hence the unambiguous assignment of the 2 structure ( Figure 1a).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations